2017
DOI: 10.22460/eltin.v5i2.p57-70
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reading Habit Towards Students’ Reading Comprehension at Private Senior High Schoolin Purwakarta

Abstract: The purpose of this research is to find out the effects of reading habit towards student’s reading comprehension. The method used is survey method. Samples were 80 students with a simple random technique. The data was collected by distributing questionnaires directly to the sample. Data analysis using descriptive statistics and the research was conducted on March to July 2015.The result showed: 1). There are any significant effects of reading habit towards students’ reading comprehension. That is proved by val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
4
0
3
Order By: Relevance
“…This finding supports the results of the previous study (e.g. Suhana & Haryudin, 2017) which reported that reading habits have a significant effect on reading comprehension. This study also yields other findings, concerning the aspects of reading habits, namely what the students read, how often they read, why they read, how they read, and time spent on reading.…”
Section: Reading Habits and Reading Comprehensionsupporting
confidence: 93%
“…This finding supports the results of the previous study (e.g. Suhana & Haryudin, 2017) which reported that reading habits have a significant effect on reading comprehension. This study also yields other findings, concerning the aspects of reading habits, namely what the students read, how often they read, why they read, how they read, and time spent on reading.…”
Section: Reading Habits and Reading Comprehensionsupporting
confidence: 93%
“…Bu nedenle anket sorularında okumaya ayrılan zaman ve okuma sıklığı dışında basılı ve çevrim içi okumayı tercih etme ile ilgili sorulara da yer verilerek yeni bir okuma çerçevesi geliştirilmiştir (OECD, 2019a). Çeşitli çalışmalarda okuma alışkanlığının okuduğunu anlama (Locher & Pfost, 2020;Sartika ve diğerleri, 2020;Suhana & Haryudin, 2017), okuma başarısı (Dökmen, 1994;Leppanen ve diğerleri, 2005;Mcgeown ve diğerleri, 2015), akademik başarı (Akın, 2016;Aksoy, 2017;Berkant & Tüzer, 2017;Cherian & Thomas, 1995;Gallik, 1999;Yılmaz, 2012;Güney ve diğerleri, 2014), okuma öz-yeterliği (Karakoç Öztürk, 2015Uyar Aydın & Balkan, 2022), yazma becerisinin çeşitli yönleri (Akın, 2016;Eminoğlu & Özkan, 2019;Dölek, 2021), beyindeki beyaz cevherin gelişimi (Takeuchi ve diğerleri, 2016), sözcük dağarcığı zenginliği (Santric ve diğerleri, 2019) ve problem çözme becerileri (Sevgi & Karakaya, 2021) ile pozitif yönde ilişkili olduğu ortaya konmuştur.…”
Section: Okumaya Yönelik Motivasyon Kaynakları Ve öğRetmen Desteğiunclassified
“…That is, a person's level of reading, writing, listening, and speaking in their first language will be similar when using a second or foreign language. In this context, a good level of reading skill may also depend on other factors such as, for instance, a person's reading habits, i.e., if someone often reads books, magazines, articles, etc., they are expected to be fast readers as well as show a high level of comprehension (Francisco and Madrazo, 2019;Septiarini, Rahmat, and Darmahusni, 2018;Suhana and Haryudin, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%